2019
DOI: 10.1186/s12889-019-6470-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication with over the counter drugs, prevalence of risky practice and its associated factors in pharmacy outlets of Asmara, Eritrea

Abstract: BackgroundAlthough over the counter (OTC) drugs are believed to be relatively safe, their inappropriate use could have serious implications. The aim of the study was to assess the practice of self-medication, prevalence of risky practice and its associated factors in pharmacy outlets of Asmara, Eritrea.MethodsA descriptive cross-sectional study was conducted among 609 customers in 20 pharmacy outlets in Asmara between August and September, 2017. Two-stage cluster sampling was employed and data were collected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
108
2
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 12 publications
(17 reference statements)
9
108
2
13
Order By: Relevance
“…10 But the prevalence was lower as compared to the study done in Pune 87.5%, 19 Nigeria 81.8% 3 and Eritrea 93.7%. 30 Additionally, the prevalence was by far greater than those findings in Ethiopia reported from different cities and town's including Sire 27.26%, 38 Addis Ababa 26.6%, 39 Mekelle University 42.67%, 13 Gondar University 38.5%, 9 Assendabo 39%, 40 Nekemte (36.7%) 41 and Jimma 27.6%. 42 The types, extent, and reason for SM might vary from place to place due to study methodological differences and variation in sociodemographic characteristics of the study participants.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…10 But the prevalence was lower as compared to the study done in Pune 87.5%, 19 Nigeria 81.8% 3 and Eritrea 93.7%. 30 Additionally, the prevalence was by far greater than those findings in Ethiopia reported from different cities and town's including Sire 27.26%, 38 Addis Ababa 26.6%, 39 Mekelle University 42.67%, 13 Gondar University 38.5%, 9 Assendabo 39%, 40 Nekemte (36.7%) 41 and Jimma 27.6%. 42 The types, extent, and reason for SM might vary from place to place due to study methodological differences and variation in sociodemographic characteristics of the study participants.…”
Section: Discussionmentioning
confidence: 68%
“…The low severity of symptoms of illness was also frequently reported in the previous study by Ali et al 8 Other studies reported different reasons for SMP. For example, cost and convenience, 16,47 cost and mildness of illness, 38 ease of accessibility and saving time 208 (24.4%), 30 and financial constraints and familiarity with medicines 10 were the major reasons of SMPs. The difference for the reasons for SMP might be due to the difference in socio-demographic factors, study setup, study design and eligibility criteria involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations